Experiences of newly qualified critical care nurses caring for post-cardiothoracic surgery paediatric patients in a private hospital in gauteng - Welhemina Molala; Charlene Downing (Elsevier, 2020)
Purpose: To gain an understanding of newly qualified critical care nurses' lived experiences in caring for post-cardiothoracic surgery paediatric patients in a private hospital in Gauteng. Background: Caring and Ubuntu are often referred to in caring for patients and their family members, yet little is known about how those processes are applied to nurses in the work environment. The researcher's assumptions about caring were based on definitions from Watson's theory (Watson, 2008:34). The core principle of this theory evolves from carative factors, the transpersonal caring relationship and caring moment. The researcher viewed a newly qualified critical care nurse as a person offering high-quality nursing to paediatric patients with congenital heart disease who require complex knowledge and advanced nursing skills. Newly qualified critical care nurses need assistance to gain knowledge and skills in this new environment. Design and methods: A qualitative, exploratory, descriptive and contextual research design was employed using Giorgi's method of data analysis. Participants were six females with ages ranging from 30 to 34 years, and they were of Black and Indian ethnicity. Data were collected employing in-depth, individual phenomenological interviews. Results: The results revealed the newly qualified critical care nurses experienced an overwhelmingly stressful environment, uncaring relationships, the participants experienced the nursing to be entirely different from nursing adult cardiac patients, and they experienced a great need for supervision and training. Participants shared their compassion, Ubuntu and transpersonal caring with patients and parents. Conclusions: Newly qualified critical care nurses need knowledge, skills and Ubuntu to offer holistic care to paediatric patients with congenital heart diseases. Nurses need to be nurtured, respected and assisted in the new environment to promote their caring consciousness. Given the clear knowledge and expertise needed in caring for paediatric patients with congenital heart disease, additional education and mentorship are needed.